PENGGUNAAN VIDEOSCRIBE TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI ENERGI KELAS VII - Sujaptio, Ramadhan (Universitas Tanjungpura, 2022)
This study aims to determine whether the use of videosribe media can improve student learning outcomes on energy materials. This research is a quantitative research. The experimental design used is a pre-experimental design in the form of a one-group pretest-posttest design. The population in this study amounted to 32 students who were in class VII C. Statistical analysis used is the Shapiro Wilk method to test the normality of the data. Meanwhile, to test the hypothesis using the paired sample t test and N-Gain Test. All calculations were processed using the SPSS version 25 program. Hypothesis test paired sample t test, obtained a significance value of 0.081 0.05. It can be concluded that there is no increase in student learning outcomes on energy material in learning at SMP Negeri 11 Pontianak after being given learning by applying the Videoscribe media. N-Gain test, the average value of N-gain is -8.4444. Based on the table, the N-gain score category according to Hake, R.R, 1999 is included in the ineffective category.